Helping hand? Aid to failing states - Chauvet, L; Collier, P (2006)
We define 'failing states' are those low-income states in which policy and governance is persistently very bad. We develop a theory of reform in these states in which several characteristics of the society might potentially be the binding constraint on change. We then introduce aid, disaggregated into technical assistance and finance, showing how it might affect these constraints. We then test our theory of aid and reform on global data. We estimate hazard functions to establish what enhances the prospects of sustained reform. We find that a proxy for the relaxation of the binding constraints postulated in the theory is highly significant. There is some evidence that both technical capacity in the society and elite interests are particularly important. Early aid has substantial but offsetting effects: technical assistance consolidates incipient reform whereas finance chills it.